Polynomial Affine Model of Gravity: After 10 Years - Oscar Castillo-Felisola; Bastian Grez; Manuel Morocho-López; Jose Perdiguero; Aureliano Skirzewski; Jefferson Vaca-Santana; Nicolas Zambra-Gómez (Universe)
The polynomial affine model of gravity was proposed as an alternative to metric and metric-affine gravitational models. What, in the beginning, was thought to be a source of unpredictability—the presence of many terms in the action—turned out to be a milestone since it contains all possible combinations of the fields compatible with the covariance under diffeomorphisms. Here, we present a review of the advances in the analysis of the model after 10 years of its proposal and sketch the guidelines for our future perspectives.